Analisis Pembelajaran Anak Aphasia dan Diskalkulia pada Siswa Kelas 4 di SD Negeri Tegal Alur 02 Pagi - Nurfadhillah, Septy; Khansa, Amalia Muthia; Firstariza, Atilla; Amelia, Dar Alifah; Rafiqh, Riyadh; Fauziyah, Rizka Nia (Lembaga Yasin AlSys, 2021)
The purpose of this study, which is to know what obstacles a teacher is facing in doing learning to aphasia and dycalculia children, what factors are a teacher's impediment to doing learning to aphasia and dykalculia children, what solutions can be made to overcoming the learning factors to aphasia and dykalculia children, If there is a difference between a specific need for children and a common child at the same time, then there is a method of learning that occurs at the meeting of the two special-needs children and general children, then the method used in this study is a defined method, which is to describe sata in accordance with the purpose and research questions. Children with special needs are those who have difficulty following the learning process because of physical, emotional, mental, social, or intellectual potential. Education inclusion is a system of education that provides opportunities for all learners who have disabilities and have the potential intelligence and special talent to pursue education or learning in the education environment together with the participants in general. Schools also need to prepare a curriculum that can be applied to learning that is acceptable to both normal students and special needs children. Based on those limits, inclusive education is intended asa system of induction services that includes children with children of their own learning ata regular school nearby.